Gendered agency in transcultural Hinduism and Buddhism: nuns, gurus and priestesses - Hüsken, Ute; Wittich, Agi; Spina, Nanette R. (Routledge critical studies in religion, gender and sexuality, 2024)
"Focusing on complex entanglements of religion and gender from a diversity of perspectives, this book explores how women enact agencies in transcultural Hindu and Buddhist settings. The chapters draw on original, in-depth empirical research in various contexts in South Asian religious traditions. Today in an increasing number of such contexts women are able to undergo monastic and priestly education, receive ordination/initiation as nuns and priestesses, and are accepted as ascetic religious leaders. They are starting to establish new religious communities within conservative traditions, occupying religious leadership positions on par with men. This volume considers the historical background, contemporary trajectories, and potential impact of the emergence of these new and powerful female agencies in conservative South Asian religious traditions. It will be of particular interest to scholars of religion, women's and gender studies, and South Asian studies"--